Рівень розвитку освіти в Україні та світі - Чиж, Б.І. (Економіко-математичне моделювання соціально-економічних систем, 2016)
This article discusses the adaptation of higher education to the European standards, norms of the Bologna process and International Standard Classification of Education, taking into account the development programs of the United Nations data. The article also examines the impact of the Human Development Index and the ranking of national systems of higher education on the level of the development of education in Ukraine.